Redefining the central serotonergic system based on genetic lineage - Jensen, Patricia (2008)
Central serotonin (5-HT, 5-hydroxytryptamine)-producing neurons are heterogeneous, differing in location, morphology, neurotoxin sensitivity and associated developmental disorders such as sudden infant death syndrome, fetal alcohol syndrome, and autism. Yet the molecular underpinnings associated with such heterogeneity and differential disease vulnerability are largely unknown, as are molecular markers capable of identifying physiological subtypes of 5-HT neurons. Here we redefine subtypes within the mature 5-HT system based on genetic programs differentially enacted and differentially required in progenitor cells. We present a molecular framework for the 5-HT neural system that, having genetic lineages as its basis, is likely to have physiological relevance and will provide a means for selectively accessing 5-HT neurons for in vivo manipulations.